Ameloblastomatous calcifying odontogenic cyst; a case report - M Seyed-majidi; K Nosrati; S Haghanifar (Isfahan University of Medical Sciences, 2009)
Introduction: Calcifying odontogenic cyst (COC) is an uncommon developmental odontogenic cyst first described by Gorlin in 1962. It is considered as extremely rare and accounts for only 1% of jaw cysts reported. Because of its diverse histopathology, there has always been confusion about its nature as a cyst, neoplasm or hamartoma.Case Report: In this report, we present a rare case of calcifying odontogenic cyst with ameloblastic proliferation, an extremely rare histologic variant, in a 15 year old female in the left mandibular molar region. The lesion was surgically removed. After enucleation and curettage, no recurrence recorded in next two years.Conclusion: Ameloblastomatous calcifying odontogenic cyst, microscopically resembles unicystic ameloblastoma except for the ghost cells and dystrophic calcifications within the proliferative epithelium. There has always been confusion about its nature as a cyst, neoplasm or hamartoma. Microscopically, this cyst shows ameloblastic proliferation in the connective tissue but no characteristics of basal cell hyperchromatism, vacuolization and nuclear polarization which is often seen in ameloblastoma, are present here. Ameloblastoma ex COC and ameloblastomatous COC are morphologically and clinically entirely different and easily distinguishable.Key words: Calcifying odontogenic cyst, Ghost cell, Gorlin Cyst, Ameloblastic proliferation